Pembelajaran Kurikulum Fungsional pada Anak Berkebutuhan Khusus di Yayasan Pendidikan Dwituna Harapan Baru Kota Medan - Vellin Syahya Jingga; Tuti Atika (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Functional Curriculum is an educational service whose approach takes into account the individual needs of students from various aspects to fulfil their future needs.  The functional curriculum is a learning design for children with special needs.  The focus of the functional curriculum is increasing independence through teaching functional life skills.  The curriculum emphasizes the life skills that children with severe cognitive disabilities need to fulfil their needs in their current and future environments.  The purpose of writing is as a result of the author's dedication after finished PKL II at the Dwituna Harapan Baru Education Foundation.  The method used is qualitative research with data collection techniques by observation and interviews.  Secondary data sources for this writing are journals and literature that can support the analysis of the discussion.  The actualization of curriculum plans or concepts, the learning process, the realization of ideas, values ​​and the process of changing student behaviour is the meaning of curriculum implementation.  The impact of functional curriculum learning on each student is different according to the abilities of each individual.  Support and guidance from family and educators is very important as a stimulus for children to learn improving their self-quality.